Introduction to policing research: taking lessons from practice - Martin, Denise (Routledge, 2024)
"This book offers a first-hand insight into the work of policing scholars and the research that they undertake. Bringing together a range of leading scholars and drawing on a range of pressing topics, it introduces the diverse nature of policing research, and the ethical and practical challenges faced by policing researchers. Each chapter brings clarity to the concept of empirical research within policing, introduces readers to the theoretical explanations and assumptions that underpin the rational of research design in policing, as well as considering the limitations of research. Topics include: -research methods in police research; -police professionalization; -police and diversity; -police leadership; -undercover policing; -police and vulnerability; -activist research; -social media and policing. This revised and expanded new edition includes more focus on the role of research in policing, police and academic partnerships and practitioners as researchers, as well as a brand new section offering international perspectives on policing research. Brimming with practical examples, case studies, key learning points and practical advice, this book is essential reading for Professional Policing students, as well as early-career researchers and those engaged with criminological research methods"--